Then and now: Reflections on two Australian mining booms - Robert G. Gregory (Institute for the Study of Labor (IZA), 2011)
Australia is experiencing its largest mining boom for more than a century and a half. This paper explores, from a national perspective, important economic differences that arise when a mining boom, such as the current one, is generated by export price increases (trading gains) rather than export volume increases. Terms of trade changes - through their direct trading gain effect and indirect real GDP effect, primarily through increased employment levels - have increased Australian living standards. The increase, relative to the US, is about 25 per cent; an increase which probably places Australian living standards well above those of the US.
urn:nbn:de:101:1-201110102168
Keywords: Q33; O11; E01; O47; C43; 330; resource booms; terms of trade; real GDP; economic growth; Bergbau; Branchenkonjunktur; Terms of Trade; Lebensstandard; Wirtschaftswachstum; Australien